Electromagnetic interactions in regulations of cell behaviors and morphogenesis - Sun, Guogui; Li, Jiong; Zhou, Wei; Hoyle, Rosalie G.; Zhao, Yue (Frontiers in Cell and Developmental Biology, 2022)
Emerging evidence indicates that the cellular electromagnetic field regulates the fundamental physics of cell biology. The electromagnetic oscillations and synchronization of biomolecules triggered by the internal and external pulses serve as the physical basis of the cellular electromagnetic field. Recent studies have indicated that centrosomes, a small organelle in eukaryotic cells that organize spindle microtubules during mitosis, also function as a nano electronic generator in cells. Additionally, cellular electromagnetic fields are defined by cell types and correlated to the epigenetic status of the cell. These interactions between tissue specific electromagnetic fields and the chromatin fibers of progenitor cells regulate cell differentiation and organ sizes. The same mechanism is implicated in the regulation of tissue homeostasis and morphological adaptation in evolution. Intercellular electromagnetic interactions also regulate the migratory behaviors of cells and the morphogenesis programs of neural circuits. The process is closely linked with centrosome function and intercellular communication of the electromagnetic fields of microtubule filaments. Clearly, more and more evidence has shown the importance of cellular electromagnetic fields in regulatory processes. Furthermore, detailed understanding of the physical nature of the inter- and intracellular electromagnetic interactions will better our understanding of fundamental biological questions and a wide range of biological processes.